2021
DOI: 10.1002/nop2.1135
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of social support and attitudes towards death: A mediator role of depression in older patients on haemodialysis

Abstract: The incidence and prevalence of end-stage renal disease (ESRD) in Taiwan ranks first in the world (Wang et al., 2018). The severity of the problem can be reflected in particularly high kidney dialysis population which is 1.6-1.8 times that of Japan and Korea, and the highest proportions of ESRD expenditure with respect to their national health insurance systems (Ismail et al., 2019; US Renal Data System, USRDS, 2017). In addition, according to the prediction by Kidney Disease: Improving Global Outcomes (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The Korean older adults have a slightly positive attitude towards death, which is consistent with the results of this study [ 36 ]. In this study, the score of neutral acceptance of death among the older adults was the highest, but still lower than positive attitude towards death (3.45 ± 0.58) among the older adults in Taiwan, China [ 37 ]. The results of this study showed that the attitude towards death in the study participants was neutral acceptance of death mainly.…”
Section: Discussionmentioning
confidence: 95%
“…The Korean older adults have a slightly positive attitude towards death, which is consistent with the results of this study [ 36 ]. In this study, the score of neutral acceptance of death among the older adults was the highest, but still lower than positive attitude towards death (3.45 ± 0.58) among the older adults in Taiwan, China [ 37 ]. The results of this study showed that the attitude towards death in the study participants was neutral acceptance of death mainly.…”
Section: Discussionmentioning
confidence: 95%